Treatment of Advanced Carcinoma of the Larynx and Hypopharynx with Laser Followed by External Radiotherapy - Lalee Varghese; John Mathew; Subhashini John; Anand Job (Iranian Journal of Otorhinolaryngology, 2017)
Introduction: Radical laryngeal surgeries for extensive laryngeal and hypopharyngeal tumors often require a permanent tracheostomy, which has an immense impact on the quality of life of patients. A minimally invasive technique such as transoral laser microresection (TLM) followed by radiotherapy can preserve the functions of the voice and swallowing. The aim of this study is to evaluate the role of laser debulking in the treatment of carcinoma of the larynx and hypopharynx, to evaluate the response of the tumor to subsequent radiotherapy, and also to assess the usefulness of laser in avoiding tracheostomy and functional preservation of the voice and swallowing.    Materials and Methods: This prospective cohort study included patients with carcinoma of the larynx and hypopharynx unwilling to have definitive surgery and those medically unfit for radical surgery. The clinical profile of patients at presentation,  tumor status following laser debulking, immediately after radiotherapy (RT), 6 weeks post RT, 3 months post RT, and at the end of study; short term complications associated with laser surgery; and usefulness of laser in avoiding tracheostomy and in functional preservation of the voice were evaluated.   Results: There were 18 (90%) male patients and 2 (10%) female patients. Age ranged from 24 to 78 years with a mean age of 55. Hoarseness of voice was the most frequent presenting complaint (90%) followed by progressive dysphagia (45%), odynophagia (40%), otalgia (40%), and dyspnoea (25%). 11 (55%) patients had T3 tumors, while 6 (30%) were T2,  and 3 (15%) were T4 lesions. 65% of  patients were free of lymph node metastasis at presentation. 2 (10%) had N1 and 5 (25%) had N2  nodes. At presentation 10 (50%) patients had Stage III disease and 6 (30%) had stage IV disease. 13 patients (65%) had moderately differentiated squamous cell carcinoma. None of the risk factors and co-morbid illnesses showed any statistically significant difference among the tumor sites. Apart from the 2 (10%) patients who had residual disease, 2 (10%) patients developed a recurrent tumor in the course of their follow up. None had neck recurrence. Two patients underwent tracheostomy, before laser surgery, for compromised airway and both had recurrence of their tumor and continued to be on tracheostomy.   Conclusion: Laser debulking followed by radiotherapy is a viable alternative in the management of malignancies of the larynx and hypopharynx for those who refuse radical surgery and for those patients in whom radical open surgery is impractical due to physiological reasons such as advanced age and poor pulmonary reserve.